The spectrographic determination of trace elements in citrus leaves,Spectographic determination of trace elements in citrus leaves - Brandt, Peter Jürgen (Rhodes University, Faculty of Science, Department of Chemistry, 1962)
From Introduction: With the rapidly growing knowledge on trace elements and their influence on plant nutrition the need for accurate and rapid methods for their determination arose. The essential plant nutrients are usually divided into two groups. The major or macronutrient elements, necessary in comparatively large amounts, and the trace or micro-nutrient elements. In the case of plants, the first group includes Sulphur, Phosphorus, Potassium, Magnesium, Calcium and Nitrogen. The essential trace elements are Iron, manganese, Boron, Copper, Zinc, Molybdenum and Chlorine. Cobalt is essential for animal nutrition as a constituent of Vitamin Bâ‚ â‚‚, but its essentiality for plants has not yet been proved. The latter group consists of metals which are catalysts in enzyme reactions and whose presence in the plant in minute amount determines whether the plant will be able to complete the vegetative or reproductive stage of its life cycle. Molybdenum may be quoted as an example of an essential trace element. It is generally recognised to be the catalyst responsible for the fixation of Nitrogen.
Keywords: Citrus; Trace elements in plant nutrition